Analysis E-Modul Using Kondular Application on Poetry Writing Material at SDN Tasikmadu 1 Malang - Endang Setyowati; Ari Nugrahani (Journey: Journal of English Language and Pedagogy, 2023)
This research aims to produce e-module using the kondular application, describe the feasibility of e-module using the kondular application, and describe the effectiveness of e-module using the kondular application in learning to write poetry in class IV SDN Tasikmadu 1. The product test design used is a product feasibility test and a test product effectiveness. The subjects of this research are divided into 2 categories, namely the feasibility test subjects consisting of validators, teachers, and class IV students at SDN Tasikmadu 1 Malang for the 2023/2024 academic year, while the effectiveness test subjects are teachers and class IV students at SDN Tasikmadu 1 Malang for the 2023/2024 academic year. This research uses the development of the ASSURE model. Data collection technique by distributing validation questionnaires to validadors. The instruments used in this research were questionnaire sheets, interview sheets and observation sheets. The data analysis technique is to calculate the average validator score during the feasibility test and effectiveness test. The result of this research is to produce teaching materials in the form of poetry emodules based on the Kondular application, where the average feasibility score from the material validator is 87%, the language validator is 90%, and the media validator is 88%, where the teaching material shows a very feasible level. and the effectiveness of teaching materials in learning to write poetry has been proven to be effective for use by fourth grade elementary school students. The response from students and teachers to this e-module using the kondular application was very positive, because the teaching material was very interesting and interactive.